DNA Repair Capacity-Related to Genetic Polymorphisms of DNA Repair Genes and Aflatoxin B1-Related Hepatocellular Carcinoma Among Chinese Population - Long, Xi-Dai; Yao, Jin-Guang; Zeng, Zhi; Huang, Cen-Han; Liao, Pinhu; Huang, Zan-Song; Huang, Yong-Zhi; Ban, Fu-Zhi; Huang, Xiao-Yin; Yao, Li-Min; Fan, Lu-Dan; Fu, Guo-Hui (IntechOpen, 2011)
None